1952
DOI: 10.1007/bf02632628
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alkali concentration and other factors on the conjugation of natural polyunsaturated acids as determined by ultraviolet absorption measurements

Abstract: Summary Optimum conditions for production of maximum conjugation of methyl arachidonate were determined. These comprise heating the sample in 21% KOH glycol for 15 minutes at 180°C. The optimum conditions of isomerization have also been applied to methyl linoleate, methyl linolenate, methyl eicosapentaenoate, and docosapentaenoate prepared by physical methods. These conditions greatly increased the sensitivity of the spectrophotometric method for all the polyun‐saturated acids except linoleic, for which the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1955
1955
1964
1964

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…Application of their optimum conditions of isomerization (18% KOtt-glyeol) more than doubled the absorptivity of araehidonic acid over that obtained by employing either method A or B. This effect of higher concentration of alkali was confirmed by Herb and Riemenschneider (19), who found however that 21% KOH-glycol was optimum for producing maximum tetraene conjugation of arachidonic acid. They also extended the investigation and determined the absorptivity constants with this reagent for linoleic, linolenie, arachidonic, and pentaenoic acids of natural configuration.…”
Section: Methods B---11% Koh-glycerol Reagent a Methodsmentioning
confidence: 74%
See 1 more Smart Citation
“…Application of their optimum conditions of isomerization (18% KOtt-glyeol) more than doubled the absorptivity of araehidonic acid over that obtained by employing either method A or B. This effect of higher concentration of alkali was confirmed by Herb and Riemenschneider (19), who found however that 21% KOH-glycol was optimum for producing maximum tetraene conjugation of arachidonic acid. They also extended the investigation and determined the absorptivity constants with this reagent for linoleic, linolenie, arachidonic, and pentaenoic acids of natural configuration.…”
Section: Methods B---11% Koh-glycerol Reagent a Methodsmentioning
confidence: 74%
“…This reagent offers the advantage of a transparent medium without using an atmosphere of nitrogen either in lhe preparation of the reagent or during the isomerization procedure. An extension of the utility of the method resulted from the determination of the absorptivity constants for pentaenoic acids when employing this reagent (19). Method C--21% KOH-glycol reagent.…”
Section: Methods B---11% Koh-glycerol Reagent a Methodsmentioning
confidence: 99%
“…Conjugation of the double bonds and examination of the ultraviolet spectrum of the conjugated isomers has been recommended as a method of determining individual constituents in mixtures of unsaturated fatty acids. A method frequently used for the more highly unsaturated fatty acids is that of Herb and Riemensehneider (5). It consists of heating the sample for 15 min.…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons that many feed users have held back on the use of fats in feed is the fact that most animals as well as poultry will not eat feed containing fats when they have become rancid except to prevent starvation. In addition to this, Quackenbush (5) of Purdue University has reported that fats which are oxidized will bring about a more rapid breakdown of the fat-soluble dietary essentials such as vitamin A, vitamin D, and vitamin K. He also reports that cases of dermatitis and failure of the reproductive organs have been reportedly caused by rancid dietary fat.…”
Section: Apolismentioning
confidence: 99%
“…This device ( Figure 2) permitted the removal of a drop of distillate at any time without interruption of the distillation. Each of the chain-length fractions obtained from the distillation of P1, P2, P3, and F was analyzed by gas-liquid chromatography, paper chromatography (15), or alkali-isomerization (8), or a combination of all three methods, depending on their complexity. From these analyses the composition of P1, P.,, P3, and F was determined (Table II) as well as the composition of the original acids.…”
Section: General Proceduresmentioning
confidence: 99%